Engineers‟ Perceptions of Diversity and the Learning Environment at Work: A Mixed Methods Study - Brenda L. Firestone (Adult Education Research Conference, 2012)
Women and people of color are particularly underrepresented in the science, technology, engineering, and mathematic (STEM) disciplines. This mixed methods study surveyed 527 engineers and interviewed eight female engineers to examine the current culture climate for diversity in engineering worksites, and how gender, race, and age intersect and affect engineers‘ perceptions of organizational inclusiveness and the learning environment surrounding diversity. Keywords: STEM, women, race, culture climate, diversity, work, mixed methods.
Keywords: STEM; women; race; culture climate; diversity; work; mixed methods